2022
DOI: 10.3390/ijerph19042082
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Dynamics and Multiscale Regression Modelling of Population Level Indicators for COVID-19 Spread in Malaysia

Abstract: As COVID-19 dispersion occurs at different levels of gradients across geographies, the application of spatiotemporal science via computational methods can provide valuable insights to direct available resources and targeted interventions for transmission control. This ecological-correlation study evaluates the spatial dispersion of COVID-19 and its temporal relationships with crucial demographic and socioeconomic determinants in Malaysia, utilizing secondary data sources from public domains. By aggregating 51,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
(57 reference statements)
2
15
1
Order By: Relevance
“…The authors explained this paradox because health care capacity can be used as a measure of a country's wealth. Unlike these results, a recent Malaysian study found no significant relationship between COVID-19 incidence and coverage of primary healthcare services ( 29 ). However, the same research explained the low number of cases in regions with low per capita income and a significant GINI coefficient, with insufficient access to health services.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The authors explained this paradox because health care capacity can be used as a measure of a country's wealth. Unlike these results, a recent Malaysian study found no significant relationship between COVID-19 incidence and coverage of primary healthcare services ( 29 ). However, the same research explained the low number of cases in regions with low per capita income and a significant GINI coefficient, with insufficient access to health services.…”
Section: Discussioncontrasting
confidence: 72%
“…Second, implementing a policy of mass testing by the government in industry and factories, and even in large nonindustrial workplaces, may have resulted in significantly higher cases reported. In addition, the low number of cases in provinces with higher poverty populations can be explained by the lack of access to testing opportunities, as argued in previous studies by (28,29).…”
Section: Discussionmentioning
confidence: 90%
“…As of late, there have been a handful of works that attempt to understand the spread of COVID-19 as well as predict confirmed cases and deaths of COVID-19, especially making use of statistical methodologies. For example, Kucharski et al [ 17 ] investigated a blend of stochastic transmission models on four data sets that caught the everyday number of new cases, the day-to-day number of new internationally sent out cases, the extent of contaminated travelers on departure flight, and the quantity of new confirmed cases to appraise the transmission elements of the illness throughout some time [ 18 ]. Machine learning-based model has been applied to analyze and predict the growth of COVID-19 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kuta District, which has the highest density level in Bandung Regency, experienced a not too significant increase in cases. However, there is an increase in mild cases with local transmission from residents in the area [28].…”
Section: Resultsmentioning
confidence: 99%